PENGARUH MINAT SISWA, LINGKUNGAN SEKOLAH DAN LINGKUNGAN KELUARGA TERHADAP MOTIVASI BELAJAR SISWA DI SMK NEGERI 4 HALMAHERA UTARA - Baeruma, Bobby Christian; Suryaputra, Ronald; Rahcmawati, Ike Kusdyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Learning motivation is a crucial factor in achieving academic success, particularly in vocational education settings such as vocational high schools (SMK). Recent field observations indicate a notable decline in student motivation, despite adequate school facilities and academic support. This issue is reflected in low classroom participation, limited enthusiasm for lessons, and minimal involvement in practical and extracurricular activities. External factors such as lack of emotional support from parents, family economic pressures, and monotonous teaching strategies further exacerbate the problem. This study aims to examine the influence of student interest, school environment, and family environment on students’ learning motivation at SMK Negeri 4 Halmahera Utara. Employing a quantitative approach with a survey method, the research involved 93 students from grades X to XII selected through simple random sampling. Data were collected using questionnaires based on validated indicators and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3. The results revealed: (1) a positive and significant effect of student interest on learning motivation; (2) a positive but not significant effect of the school environment; and (3) a positive but not significant effect of the family environment. Among the variables, student interest showed the strongest contribution. The findings suggest that enhancing learning motivation requires integrated efforts, including fostering student interest, cultivating a supportive school climate, and encouraging active family involvement. The results provide valuable input for schools, educators, and parents in formulating more effective, student-centered educational strategies.